2020
DOI: 10.32479/ijeep.8490
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Performance and Firm Value: Testing the Role of Firm Reputation in Emerging Countries

Abstract: This study aims to analyze the empirical evidence about the effect of environmental performance on firm value mediated by firm reputation in emerging countries. The sample of this study is the mining industry sectors listed on the Indonesia Stock Exchange from 2015 to 2018. The data is analyzed using partial least squares based structural equation modeling with WarpPLS 6.0 software. The results show that environmental performance has a positive and significant effect on firm reputation. In contrast to the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 11 publications
2
22
0
4
Order By: Relevance
“…Several experimental findings in previous literature indicate that environmental performance positively affects organizational performance. Khanifah et al (2020) also contended that businesses expect investors to react positively to their reputation as an organization to attract them to invest more capital in the firms, increasing their organizational performance and bringing the investors benefits and enhancing their strong value. However, the firms had better respond favourably to government regulations for environmental pollution than to take an active role in environmentally friendly activities to establish an organizational reputation and improve commercial efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental findings in previous literature indicate that environmental performance positively affects organizational performance. Khanifah et al (2020) also contended that businesses expect investors to react positively to their reputation as an organization to attract them to invest more capital in the firms, increasing their organizational performance and bringing the investors benefits and enhancing their strong value. However, the firms had better respond favourably to government regulations for environmental pollution than to take an active role in environmentally friendly activities to establish an organizational reputation and improve commercial efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Abdirahman, Sauvee [20], Devi and Hemant [8], Fadun [21], Jenkins [22], Karen and Linh [23], Khanifah, and Udin [24] have shown that the ineffectiveness of CSR assistance for empowering SMEs was not yet in line with CSR programs and the real needs felt by SMEs. Hadi and Khanifah [25] have revealed that the determination of program strategies and the determination of CSR's dimensions or elements had a vulnerability to CSR's effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Kao et al (2010) suggested enterprises employing proactive environmental friendly practices could obtain superior environmental performance and the findings reveal empirical evidence that environmental performance positively affects organizational performance. Likewise, Khanifah et al (2020) argued that, enterprises are expecting a positive reaction of investors to their organizational reputation, aimed at drawing them to spend more capital into the enterprises, which can improve organizational performance, bring profits for the investors, and enhance their firm value. Instead of trying to avoid the investment in environmental friendly systems; enterprises had better positively react to the governmental rules of environmental pollution as well as actively take part in environmental friendly actions to build up organizational reputation and develop business effectiveness.…”
Section: Effect Of Environmental Performance On Organizational Performancementioning
confidence: 99%